Efektivitas Penerapan Konsinyasi dalam Pemberian Ganti Rugi Pengadaan Tanah - Setyawahyuningtyas, Lucia (Jurnal Hukum Caraka Justitia, 2023)
The land is one of the natural assets controlled by the State of Indonesia as stipulated in Article 33 paragraph (3) of the 1945 Constitution. The word control has the meaning of being authorized to regulate by issuing statutory regulations. Even so, land problems are still a problem that often occurs in society, especially related to land acquisition for public purposes and accompanied by compensation. The purpose of this study is to the extent to which the effectiveness of the application of consignment in the provision of compensation due to land acquisition. The research method in this writing uses a normative juridical approach and data analysis used is qualitative and data collection is carried out by collecting primary, secondary, and tertiary materials.Based on the results of the analysis of this writing, the application of consignment in the provision of compensation for land acquisition can be the final way in resolving disputes between the government/institution/agency and the community when there is no agreement due to various factors such as the owner or heirs not being present and difficult to communicate related with land acquisition for public interest or this disagreement is due to the absence of an agreement on the amount of compensation in which compensation for land acquisition is considered too small so that it cannot meet further needs. The consignment request is carried out by the Debtor/Agency/Institution/Government to deposit compensation money through the local District Court and of course, use the applicable provisions as stipulated in the Law so that it has permanent legal force.